Menelaah Pembagian Profesi Catur Warna ditinjau dari Implementasi Ajaran Catur Asrama - Tardi Edung (Dharma Duta, 2019)
Social change is bound to happen and this continues as long as there is life on this earth. Increasing the individual's social status in society occurs in accordance with the profession occupied, change and increase one's position is absolutely there. How is the social status of an individual seen from the teachings of boarding chess. The problematic of life is quite diverse and complex, requiring individuals to live governed by the rules, norms and rules that exist in that society and none of them may deny it. Caste is the profession of a person in society who forms themselves in groups, natural arrangements. Color / caste depicts the characteristic spirit which is synthesis in Hindu mind with belief towards collaboration from race and cooperation from culture, caste system is the result of tolerance and belief. On the other hand racial color / caste is the emphasis of definite differences in human groups that cannot possibly be erased or destroyed by social change. This teaching determines whether an individual is respectable or not in his position in a homogeneous and multicultural society based on values ​​and norms as a rule of life. Transition of individual social status is adjusted to the profession occupied in society, both based on knowledge, appreciation in the form of honor and power. Changes in the profession can occur because of science, maturation of a household, self-introspection and leaving all positions in this world to more complex stages. Boarding Chess gives direction to the position of individuals in society